The Coming Revolution of Peer Production and Revolutionary Cooperatives. A Response to Michel Bauwens, Vasilis Kostakis and Stefan Meretz - Jakob Rigi (tripleC: Communication, Capitalism & Critique)
This article agrees with Meretz (2014) that the peer producing cooperatives which are proposed by Bauwens & Kostakis (2014) will become parts and parcels of the capitalist economy. Further, it argues that the so called Peer Production Licenses (PPL), originally designed by Dmitry Kleiner (2010), which is the basis of their proposal is a rent seeking instrument. Contra Bauwens & Kostakis, it argues that, from the perspectives of both reform and revolution, GPL is profoundly anti-capitalist. The article critiques Meretz`s understanding of exchange and reciprocity, on the one hand, and his underestimation of GPL`s communist aspect, on the other. On the positive side, the article, explicating the communist nature of GPL-oriented peer production, speculates about the general contours of a society where peer production is the dominant mode of production. The technological basis of this society, the article suggests, will be digital copying and automation. Spatially, it will be based on localities that transcend the current division between the city and country, synthesising agriculture with industrial, affective and symbolic production. The rise of a globally unified revolutionary social struggle which adopts peer production as its platform is indispensible for the transformation of capitalism into such a society.  A global network of revolutionary peer producing cooperatives which break with market and reduce their relations to it to an absolutely unavoidable necessary minimum can be a significant component of this social struggle. The building of these revolutionary cooperatives requires a massive exodus from the city to the country.